The effectiveness of guava (Psidium guajava) and senduduk leaves (Melastoma malabathricum L.) extract gel towards the inflammation markers and collagens on induced male rats (Sprague Dawley) with diabetes - Maigoda, Tonny Cortis; Refdanita,; Idramsyah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aimed to measure the effectiveness of a mixed extract gel from Melastoma malabathricum L. (ML) and Psidium guajava leaves (PG) on inflammatory markers and collagen distribution wound tissue in rats (Sprague Dawley) induced with diabetes. This was an experimental study with a randomized block design to 20 male rats divided into 4 treatment groups. Group 1 is negative control (gel blank), Group 2 is positive control (clindamycin gel), Group 3 used 4% gel formula mixture of ML + PG leaves, and Group 4 used 6% gel formula, a mixture of ML + PG leaves extract the gel. The results showed that there was a significant difference (p<0.001) in total Tumor Necrosis Factor-alpha (TNF-α) treated with 6% extract gel (ML + PG) from a level of 25.0 pg/mL on the 2nd day to 1.68 pg/mL on the 6th day. The smallest wound diameter was 0.75 mm2 as observed on the 6th day in rats treated with 6% extract gel (ML + PG). The largest distribution of collagen area was 219,8 (86,2%) treated by 6% extract gel (ML + PG).